The Role of MYC2 Transcription Factors in Plant Secondary Metabolism and Stress Response Mechanisms - Tuo Zeng; Han Su; Meiyang Wang; Jiefang He; Lei Gu; Hongcheng Wang; Xuye Du; Caiyun Wang; Bin Zhu (Plants)
Jasmonates (JAs) are essential signaling molecules that orchestrate plant responses to abiotic and biotic stresses and regulate growth and developmental processes. MYC2, a core transcription factor in JA signaling, plays a central role in mediating these processes through transcriptional regulation. However, the broader regulatory functions of MYC2, particularly in secondary metabolism and stress signaling pathways, are still not fully understood. This review broadens that perspective by detailing the signaling mechanisms and primary functions of MYC2 transcription factors. It specifically emphasizes their roles in regulating the biosynthesis of secondary metabolites such as alkaloids, terpenes, and flavonoids, and in modulating plant responses to environmental stresses. The review further explores how MYC2 interacts with other transcription factors and hormonal pathways to fine-tune defense mechanisms and secondary metabolite production. Finally, it discusses the potential of MYC2 transcription factors to enhance plant metabolic productivity in agriculture, considering both their applications and limitations in managing secondary metabolite synthesis.